2023
DOI: 10.1101/2023.09.24.558528
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virulence patterns of oat crown rust in Australia - season 2022

Eva C. Henningsen,
David Lewis,
Duong T. Nguyen
et al.

Abstract: Puccinia coronataf. sp.avenae(Pca) is an important foliar pathogen of oat which causes crown rust disease. The virulence profile of 48Pcaisolates derived from different locations in Australia was characterised using a collection of oat lines often utilised in rust surveys in the USA and Australia. This analysis indicates thatPcapopulations in Eastern Australia are broadly virulent, in contrast to the population in Western Australia (WA). Several oat linesPcgenes are effective against all rust samples collected… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…As reported earlier (Henningsen et al 2023), a higher virulence frequency was observed in the Pca isolates from Eastern Australia (QLD, NSW, VIC, and SA) than in those from…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…As reported earlier (Henningsen et al 2023), a higher virulence frequency was observed in the Pca isolates from Eastern Australia (QLD, NSW, VIC, and SA) than in those from…”
Section: Resultssupporting
confidence: 83%
“…As reported earlier (Henningsen et al 2023), the Pca subpopulation from Eastern Australia (QLD, NSW, VIC, and SA) exhibited a higher frequency of virulence phenotypes compared to the Pca isolates from Western Australia (WA) towards oat differential lines from both the USA ( p = 0.00059) and Australian ( p = 0.00088) sets ( Figure S1 ). Oat cultivars Barcoo, Saia, and the differential line Pc63 exhibited resistance to all 25 Pca isolates, whereas certain oat lines, such as Swan, Ukraine, Marvelous, Santa Fe, Trispernia, Landhafer, Bondvic, Pc45, Pc54, and Pc67 displayed susceptibility to the majority or all isolates.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations